THE INFLUENCE OF KNOWLEDGE AND RELIGIOSITY ON HALAL SKINCARE BRAND PURCHASE DECISION: GENERATION Z PERSPECTIVE - Nanda, Annisa Amalia Eka; Ridlwan, Ahmad Ajib; Yasin, Ach.; Nurafini, Fira (Cahaya Ilmu Bangsa, 2024)
The beauty industry is growing very rapidly in Indonesia in the market segment with a market volume of 3.16 USD in 2022 with Gen Z as the dominating market share that creates certain consumer behaviors that create purchasing decisions. This study aims to determine whether there is an influence of knowledge and religiosity on purchasing decisions mediated by attitude. The research method used in this study is a quantitative approach with primary data. The data collection technique used in this study is a data collection technique using questionnaires. The results of this study show knowledge and religiosity affected to purchasing decisions of halal avoskin beauty skincare products by Gen Z in Surabaya.